The Role of Lecturers in Soft Skill Development Strategies and Character Building in Higher Education - Aisyah, Siti; Rahayu, Yuna Mumpuni (Jurnal Edusci, 2025)
Background. Lecturers have a crucial role as supervisors and educators in forming independent character in all students. Lecturers are required to play a role in developing behavior, attitudes, competitiveness, and independent abilities in facing future challenges. Aims. This paper aims to discuss the role of lecturers in developing soft skills and character formation in higher education. Method. The method employed is a literature review from various sources, combined with the author's and lecturer's experience. Result. Lecturers are required to play an essential role in encouraging student participation and assigning relevant assignments. The exemplary nature of lecturers can increase motivation to learn, encourage students to behave well, and help them achieve educational goals that align with the expected positive values. Lecturers with integrity will provide real-life examples of truth, honesty, and consistency between their actions and the values they adhere to. Conclusion: To fulfill the role of lecturers in character formation, 10 types of soft skill development strategies need to be implemented in higher education learning. Implementation. Strategic steps for lecturers in character formation and software improvement need to be applied to all universities, both public and private